2017
DOI: 10.1038/srep45254
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic nematodes in agricultural areas in Brazil

Abstract: Entomopathogenic nematodes (EPNs) (Steinernematidae and Heterorhabditidae) can control pests due to the mutualistic association with bacteria that kill the host by septicemia and make the environment favorable for EPNs development and reproduction. The diversity of EPNs in Brazilian soils requires further study. The identification of EPNs, adapted to environmental and climatic conditions of cultivated areas is important for sustainable pest suppression in integrated management programs in agricultural areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 49 publications
2
31
1
1
Order By: Relevance
“…Campos-Herrera et al (2019) recently published a first report of H. indica in a Mediterranean region, in a survey conducted in Portugal. Species variety in the present study was low compared to previous studies of natural populations worldwide 32,34,37,38,43 . This might be due to aggregated spatial distributions of the species, which is a well-known distribution pattern for EPNs 18,33,35 .…”
Section: Isolation and Characterization Of Natural Epn Populationscontrasting
confidence: 87%
See 1 more Smart Citation
“…Campos-Herrera et al (2019) recently published a first report of H. indica in a Mediterranean region, in a survey conducted in Portugal. Species variety in the present study was low compared to previous studies of natural populations worldwide 32,34,37,38,43 . This might be due to aggregated spatial distributions of the species, which is a well-known distribution pattern for EPNs 18,33,35 .…”
Section: Isolation and Characterization Of Natural Epn Populationscontrasting
confidence: 87%
“…To enrich the genetic pool, natural EPN populations were collected from different habitats across Israel. Abiotic factors are known to have strong effects on EPN occurrence, persistence and species variation [32][33][34] . However, previous studies conducted worldwide have shown varied correlations between effects of habitat parameters and EPN occurrence [35][36][37] .…”
Section: Isolation and Characterization Of Natural Epn Populationsmentioning
confidence: 99%
“…Also noted in Italy were S. feltiae and H. bacteriophora , which were found to be related with vegetation habitat (Tarasco et al ., 2015). In Brazil, Heterorhabditis amazonensis , Metarhabditis rainai , Oscheius tipulae and Steinernema rarum were isolated from soil in agricultural areas (de Brida et al ., 2017). Oscheius onirici was also isolated from a wild cranberry marsh in Jackson County, Wisconsin, USA (Ye et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between habitat and abundance of entomopathogenic nematodes had been reported by a number of workers. The high rate of occurrence is reported in disturbed habitat with high human impacts like agricultural fields (Campos-Herrera et al 2007;de Brida et al 2017), whereas, it is higher in natural habitats (Stock et al 2008;Valadas et al 2014). It is thus obvious that the occurrence of EPNs relative to the habitat type varied among the species, and also depending on the geographical areas.…”
Section: Discussionmentioning
confidence: 99%